1997
DOI: 10.1093/mnras/290.4.l65
|View full text |Cite
|
Sign up to set email alerts
|

Rapid infrared flares in GRS 1915+105: evidence for infrared synchrotron emission

Abstract: We report imaging photometry of the radio-jet black hole candidate source GRS 1915+105 in the infrared K band. The observations reveal rapid infrared flare events on timescales of less than an hour. These events are strikingly similar to those regularly observed in radio monitoring at 15 GHz. Furthermore, when dereddened, the infrared events have comparable amplitudes to the radio oscillations, and observations at 15 GHz made ∼ 8 hr after our infrared observations reveal that the source was indeed displaying r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
121
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(132 citation statements)
references
References 16 publications
10
121
1
Order By: Relevance
“…This result and the derived A K = 3.3 mag (using A v A K from Rieke & Lebofsky 1985) as well, are still used for dereddening (e.g. Fender et al 1997;Fender & Pooley 2000), although the authors pointed out that these results are uncertain (Fender & Pooley 2000). The position of GRS 1915+105 is known very accurately since the discovery of the radio counterpart ).…”
Section: Grs 1915+105 and Its Optical Extinctionmentioning
confidence: 87%
“…This result and the derived A K = 3.3 mag (using A v A K from Rieke & Lebofsky 1985) as well, are still used for dereddening (e.g. Fender et al 1997;Fender & Pooley 2000), although the authors pointed out that these results are uncertain (Fender & Pooley 2000). The position of GRS 1915+105 is known very accurately since the discovery of the radio counterpart ).…”
Section: Grs 1915+105 and Its Optical Extinctionmentioning
confidence: 87%
“…Fender et al (1997) observed rapid flares in the radio and infrared, and found a clear correlation between the two. They interpreted these oscillations as synchrotron emissions from repeated ejection of matter from the system.…”
Section: Introductionmentioning
confidence: 84%
“…GRS 1915ϩ105 exhibits a broad range of correlated multiwavelength variability, including very complex Xray behavior (see, e.g., Muno, Morgan, & Remillard 1999;Markwardt et al 1999;Lin et al 2000), superluminal radio outflows (Mirabel & Rodriguez 1994;Fender & Pooley 2000), and correlated infrared, X-ray, and radio variability (Fender et al 1997;Eikenberry et al 1998;Bandyopadhyay et al 1998). Motivated by the discovery of a second high-frequency QPO in GRO J1655Ϫ40, we analyzed the archival RXTE data from GRS 1915ϩ105 to search for a second QPO in this object as well.…”
Section: Introductionmentioning
confidence: 99%